Magnetyzm miłości bliźniego w filmach "Niebieski", "Kadysz dla przyjaciela" i "Maria Magdalena" = The magnetism of love of neighbor in the movies "Three Colours: Blue", "Kaddish for a friend" and "Mary Magdalene" - Taraszczuk, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article analyzes the phenomenon of good on the example of three film works created in the last thirty years: "Trois couleurs: Bleu" ("Three Colours: Blue") by Krzysztof Kieślowski (1993), "Kaddisch fur einen Freund" ("Kaddish for a friend") by Leo Khasin (2012) and "Mary Magdalene" by Garth Davis (2018).
Keywords: Bóg; charyzma; dobro; emigrant; harmonia; miłosierdzie; miłość; miłość bliźniego; muzyka; pokój; przyjaźń; sacrum; sztuka; świętość; uchodźca; wiara; wielokulturowość; wizjoner; wojna; wyznanie; wzór do naśladowania; zbawienie; art; charisma; charity/love of neighbor; confession; émigré; faith; friendship; God; good; harmony; holiness; love; mercy; multiculturalism; music; peace; refugees; role model; sacred; salvation; visionary; war